PENGARUH KEMANFAATAN NPWP, PEMAHAMAN WAJIB PAJAK, KUALITAS PELAYANAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Pada UMKM Di Kabupaten Kendal) - Rossy Alawiyah Drajat, 11.05.62.0012; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2014)
This research aimed to analyze the effect of the benefits of TIN, taxpayer understanding, quality of services, and tax penalties on tax compliance. The population in this research are all taxpayer Micro, Small and Medium Enterprises (SMEs) in Kendal. Primary data collection method used is a survey method using questionnaires media. Sampling was done by convenience sampling method. The number of questionnaires that can be analyzed is 92 questionnaires. Data analysis techniques used in this research is multiple linear regression analysis. The results of this research showed that the benefits of TIN had positive and not significant effect on tax compliance. Taxpayer understanding,quality of service, tax penalties and tax compliance had positive and significant effect on tax compliance.Keywords: benefits of TIN, taxpayer understanding, quality of service, tax penalties and tax compliance